The contributions of public-listed organizations to knowledge-based development in Malaysia - Raja Kasim, Raja Suzana; Md. Sail, Rahim
The paper was designed to examine the contributions of knowledge management practices to knowledge-based development in Malaysia. Several salient drivers from knowledge management practices to be successful in crafting quality strategy among private organizations in Malaysia had been identified. The proactive use of knowledge management practices facilitates the strategy of these private organizations and lead to better contribution to the development of knowledge-based activities. This paper makes a proposition for the structuring of knowledge management concept. For example, an extensive consideration and utilization of knowledge management practices among private organizations would promote greater support for knowledge-based development to be materialized in Malaysia. In addition, this theory-building indicates various forms of knowledge issues highlighting the acquisition, dissemination and response to knowledge-related activities and affect the performance of the private organizations subjectively. The multiple regression test on knowledge management practices was found not only to exert a significant positive influence on the performance of private organizations in Malaysia, but also serves as a more important predictor of organizational performance in stimulating knowledge-based moves in the country. Nevertheless, an important implication of this paper is the limited function of an individual responsible in integrating knowledge issues in crafting organizational strategy because of narrow stereotypical views regarding the needs of k-based views in terms of successful nation knowledge-based development.